Critical religion and critical research on religion: Religion and politics as modern fictions. (December 2015) - Fitzgerald, Timothy
The purpose of this response piece is to summarize what is meant by "critical religion" as a contribution to the ongoing debates within the discipline, and specifically in relation to critical research on religion.